A Meta-Analysis of PCSK9 Inhibitors Versus Statins for LDL Cholesterol Reduction and Cardiovascular Outcomes - Adlan, Altayeb Osman Saad; Kandy, Muhammad Shazin Vatta; Almaliti, Tala N.; Shajahan, Ansalna; Zubedi, Mohamed Bin Abdur Rub; Atraqchi, Abbas Ammar; Abouhelwo, Nada Ahmed; alnajjar, bashayer abdulla; Mansoor, Mazna (Cardiology and Cardiovascular Medicine, 2025)
Background: Statins have always been the mainstay of treatment of high LDL cholesterol (LDL-C), however, they are not suitable in all cases. Statin intolerance or inadequate LDL-C control are common in patients. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors are effective lipid-lowering substitute with potential cardiovascular advantage. Objective: To compare the safety and efficacy of PCSK9 inhibitors and statins in reducing LDL-C and preventing cardiovascular events. Methods: In this meta-analysis, peer-reviewed and recent studies were analyzed to generate result. A random-effects model was used to extract and synthesize effect sizes (log odds ratios). We calculated pooled odds ratios (ORs), 95% confidence intervals (CI) and heterogeneity (I²). Additionally, subgroup analysis was carried out. Results: With a statistically significant decrease in cardiovascular outcomes (OR = 1.79; 95% CI: 1.72–1.86), the pooled OR favored PCSK9 inhibitors. Nonetheless, there was a lot of variation among the studies (I2 = 80.2%). Conclusion: Compared to statins, PCSK9 inhibitors significantly reduce LDL-C and prevent cardiovascular events. Variability among studies indicates that timing, combination therapies and patient-level factors affect results.